2022
DOI: 10.1097/md.0000000000030382
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of preoperative P-CRP in patients with osteosarcoma: A retrospective study of 101 cases

Abstract: This study aimed to investigate the value of the product of peripheral blood platelet and serum C-reactive protein (P-CRP), an inflammatory indicator, for the prognosis of patients with osteosarcoma. Patients with osteosarcoma who were diagnosed and treated at the First Affiliated Hospital of Guangxi Medical University, China, between January 2012 and December 2019 were included in this retrospective study. Receiver operating characteristic curves were used to calculate the optimal cut-off values for inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Fourteen independent clinical studies conducted specifically on OS have shown that the higher an NLR becomes, the shorter the survival becomes [294][295][296][297][298][299][300][301][302][303][304][305][306]. The extraordinary nature of this association of a higher NLR with a shorter survival in adult and pediatric OS should be fully appreciated.…”
Section: Ticomentioning
confidence: 99%
“…Fourteen independent clinical studies conducted specifically on OS have shown that the higher an NLR becomes, the shorter the survival becomes [294][295][296][297][298][299][300][301][302][303][304][305][306]. The extraordinary nature of this association of a higher NLR with a shorter survival in adult and pediatric OS should be fully appreciated.…”
Section: Ticomentioning
confidence: 99%